Graduated Compression Stockings for Deep Vein Thrombosis prevention in Surgical Patients: A Systematic Review - Pratama, Dedy; Simatupang, Satria M.H (UI Scholars Hub, 2022)
Introduction. Oral anticoagulant therapy is commonly used to prevent deep vein thrombosis (DVT). However, it might increase the risk of intraoperative and postoperative bleeding. Graduated compression stockings (GCS) reduced DVT risk, but there is a lack of supporting evidence. Thus, the study aimed to find the efficacy of GCS compared to the pharmacological method in high-risk surgical patients. Method. Literature search proceeded in Cochrane, ClinicalKey, and PubMed. Using keywords graduated compression stockings